Risk factors related to pressure injury in COVID-19 patients in intensive care unit: integrative review (Research, Society and Development, 2023)
Objective: To identify the main risk factors that are related to the development of PI in COVID-19 patients in the ICU. Method: This is an integrative review study with a qualitative and quantitative approach, carried out between February 14, 2023 and March 1, 2023, using the following databases: VHL, LILACS, MEDLINE, SciELO, PUBMED and CINAHL, of the last 5 years. Results and Discussion: The search resulted in 904 publications, after filtering based on the inclusion and exclusion criteria, reading the titles, abstracts and full articles, the sample consisted of 10 articles. The sample size included a population of 4087 patients diagnosed with COVID-19 and who had PI. The greater predominance of PI in the study was among males (n=2140), compared to females (n=1647), with the sacral region being most affected with 34%, followed by the nasal region with 21% and the gluteal region with 16 %. People aged over 60 years and previous comorbidities were identified as risk factors. In addition to the use of hospital devices, pronation, long hospitalization, use of vasopressors, sedatives and anesthetics, two other factors include hypoalbuminemia and hemoglobin. Final Considerations: COVID-19 patients being treated in the ICU generally presented a combination of intrinsic and extrinsic factors for the onset of PI. The present study serves as a subsidy for health professionals, both for prevention and decisions on conduct and provision of quality care and risk reduction for the patient.